1995
DOI: 10.1063/1.360278
|View full text |Cite
|
Sign up to set email alerts
|

Paramagnetic defects induced by mechanical stress in calcium sulfide phosphor

Abstract: The effect of uniaxial pressing and grinding on pure and europium-doped CaS powders prepared by the alkaline polysulfide flux method is studied by electron spin resonance (ESR). F+ centers are generated in the bulk of CaS particles and their ESR spectra can be easily separated from those of other paramagnetic species by using a 90" out-of-phase detection. This is possible because of the very long transverse relaxation time Ts of F+ centers. It is thought that the primary defects induced by mechanical stress ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 46 publications
2
23
0
Order By: Relevance
“…This was because grinding strongly influences the intrinsic point defect concentration, which leads to a decrease of the emission intensity. 26 This phenomenon has also been observed for europium-doped CaS 26 and rare-earth-metal oxysulfides. 27…”
Section: Resultsmentioning
confidence: 81%
“…This was because grinding strongly influences the intrinsic point defect concentration, which leads to a decrease of the emission intensity. 26 This phenomenon has also been observed for europium-doped CaS 26 and rare-earth-metal oxysulfides. 27…”
Section: Resultsmentioning
confidence: 81%
“…There is no clear evidence of any Mn 2+ signal initially present in the native sample, in contrast to previous reports. [12,15] A magnified view of the low field |m I | = 5/2 signal is provided in Figure S3 (Supporting Information) for reference.…”
Section: Cw X-band (9 Ghz) Epr Spectra Of Commercial Cas:eu Phosphorsmentioning
confidence: 99%
“…Clearly, due to the influence of particle size, morphology, and levels of defects or impurities on the photoluminescent properties of the material, the synthesis method and any subsequent treatments require careful consideration, since subtle changes in the experimental conditions can have a substantial effect on the final functional properties of the material. A number of studies have reported the presence of various intrinsic point defects in these alkaline earth sulfides, [12,[15][16][17][18] such as S 2− vacancies, which can act as shallow electron traps (≈0.26 eV) below the conduction band of CaS. [16] Other S 2− vacancies, stabilized by Ca 2+ interstitial centers, were also evidenced by EPR and thermoluminescent measurements.…”
Section: Introductionmentioning
confidence: 99%
“…The idea about the aggregates of cation± anion vacancies was only mentioned but not proved, as data on cation vacancies were absent at that time, and the centres observed had not been investigated thoroughly. Similar EPR signals were detected later [6] in plastically deformed CaS. The EPR lines of F À c centres were not resolved, and some other line of a defect with a different thermal stability was included into the spectrum.…”
Section: Introductionmentioning
confidence: 52%